Foreign youth in prison: Invisible population in the dynamics of social exclusion - García-España, Elisa (My University, 2023)
Spain has been a territory of arrival of foreign unaccompanied minors since the 1990s. A growing concern, as the number of minors arriving from Morocco continuing to grow, is their protection and social inclusion, especially after they reach the age of 18. Once they have come of age, resources for support and protection are scarce. Exploratory research in the province of Malaga (Spain) identified a considerable number of foreigners who are former foster youths in prison, but there is no record of this group in the statistics of penitentiary institutions. The aim of JEPRAN project (Former Foster Youths in Andalusian Prisons, 2021 -2023) is to visualize the challenge faced by Andalusian society in the inclusion of former foster youths and to identify the social and legal crossroads they encounter during their migration path and transition to adulthood. At the Andalusian level, the JEPRAN project will seek to identify how many of the young people in prison are foreign who have been fostered by the child protective services. Our hypothesis is that this group are overrepresented, and we aim to identify risk and protection variables in comparison with young people released from prison. Bearing in mind that this is an ongoing project, this presentation seeks to discuss from a methodological perspective the strategies and difficulties encountered during fieldwork with an invisible population, as well as presenting the preliminary results of this research.
Keywords: Derecho público - Congresos; Imprisonment; immigration detention